2015
DOI: 10.1002/2014ja020714
|View full text |Cite
|
Sign up to set email alerts
|

Outflow of low‐energy ions and the solar cycle

Abstract: Magnetospheric ions with energies less than tens of eV originate from the ionosphere. Positive low-energy ions are complicated to detect onboard sunlit spacecraft at higher altitudes, which often become positively charged to several tens of volts. We use two Cluster spacecraft and study low-energy ions with a technique based on the detection of the wake behind a charged spacecraft in a supersonic ion flow. We find that low-energy ions usually dominate the density and the outward flux in the geomagnetic tail lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(119 citation statements)
references
References 62 publications
6
113
0
Order By: Relevance
“…Moreover, integrated over the polar cap area, these H + flux densities lead to fluxes similar to those found by other studies of the polar wind (see e.g. Nagai et al, 1984;Cully et al, 2003;Huddleston et al, 2005;Engwall et al, 2009;André et al, 2015).…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, integrated over the polar cap area, these H + flux densities lead to fluxes similar to those found by other studies of the polar wind (see e.g. Nagai et al, 1984;Cully et al, 2003;Huddleston et al, 2005;Engwall et al, 2009;André et al, 2015).…”
Section: Methodssupporting
confidence: 85%
“…Cully et al (2003) using Akebono data, however, observed an increase for both H + and O + , of ∼ 300 and ∼ 2000 %, respectively. Furthermore, Engwall et al (2009) and André et al (2015) found an increase of the ion total flux of ∼ 200 and ∼ 100 %, respectively. It is worth mentioning that Yau et al (1988) and Cully et al (2003) were restricted to an energy range of ∼ 10 eV-17 keV and ∼ 1-70 eV, respectively, and Engwall et al (2009) and André et al (2015), using an indirect method involving the spacecraft potential, should have theoretically observed all ions.…”
Section: Variations Compared To Other Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…A supersonic flow of positive low-energy ions can create an enhanced wake behind a positively charged spacecraft. Here the ions are diverted by the potential structure and not by the much smaller spacecraft (Engwall et al 2006(Engwall et al , 2009b(Engwall et al , 2009aAndré and Cully 2012;André et al 2015). The conditions for the enhanced wake formation sketched in Fig.…”
Section: Ionospheric Plasma Transportmentioning
confidence: 94%
“…Using the Cluster dataset and this unique method to obtain low-energy ion fluxes in the night-side (X GSM < 0) André et al (2015) showed the occurrence rate of low-energy ions was 60-70 % in the lobes to out to X GSM of about 15 R E during all parts of the solar cycle, as indicated in Fig. 13.…”
Section: Ionospheric Plasma Transportmentioning
confidence: 99%